Bridging the Geographic Information Sciences International AGILE'2012 Conference, Avignon (France), April, 24-27, 2012 - Gensel, Jérôme; Josselin, Didier; Vandenbroucke, Danny (Lecture Notes in Geoinformation and Cartography, 2012)
For the sixth consecutive year, the AGILE conference promoted the publication a book collecting high-level scientific contributions from unpublished fundamental scientific research. The papers published in the AGILE 2012 LNG&C volume contribute substantially to Geographical Information Science developments and to the success of the 15th AGILE conference (Avignon, France, 24-27April, 2012) under the title 'Bridging the Geographic Information Sciences'. This year's conference emphasizes that geoinformation science, geomatics and spatial analysis are fields in which different disciplines, epistemologies and scientific cultures meet. Indeed, the scientific articles published in this volume cover a wide diversity of GIScience related themes, including: Spatio-temporal Data Modelling and Visualisation; Spatial Data Infrastructures; Geo Web Services and Geo Semantic Web; Modelling and Management of Uncertainty; Spatio-temporal Data Quality and Metadata; Mobility of Persons, Objects and Systems, Transports and Flows; Spatial Analysis, Geostatistics, and Geo Information Retrieval; Modelling and Spatial Analysis of Urban Dynamics, Urban GIS; GIS and Spatial Analysis for Global Change Modelling, Impact on Space; and Geographic Information Science: links with other disciplines and people.